PENINGKATAN KEPERCAYAAN DIRI (SELF-EFFICACY) DAN MOTIVASI SISWA MELALUI MODEL DISKUSI DI SMP N 1 MLATI - Hayu, Wiworo (Jurnal Penjaminan Mutu, 2023)
This research aims to determine the increased self-efficacy and the learning motivation of students through the application of meaningful discussions using the model. The research was practiced in the SMP N 1 Mlati. The subject of this study was class VIIB. This type of study is a Class Action Research (PTK) with the assessment cycle model Spiral Kemmis and Taggart are planning, acting and observing, and reflecting. Data collection techniques increase self-efficacy were measured by questionnaires, improved student motivation is measured by questionnaires and observation sheets used to process of increasing self-efficacy and student motivation. Data analysis technique used is descriptive qualitative and quantitative. The results showed that increasing students’ self-efficacy and students’ motivation, namely (1) Establishing the set: discuss the purpose of discussion and sharing of students in 6 groups, (2) focus the discussion: confirms discussions with the group, the initial question about the problems in about, the problems presented deals with everyday life, focusing a good discussion, (3) control the discussion: facilitated discussion with questions, to guide each group discussion, respond to ideas, firmly beginning to end, write the results of discussions on the board with the obvious; (4) end the discussion: riview, summarizes and concludes the discussion with the students and write on the board, and (5) debriefing: ask the opinion of students about his way discussions, the opportunity to participate, revering others' ideas and difficult discussions. Students have the self-efficacy to achieve success indicators to all students (100%) have a high self-efficacy. Students are motivated to achieve success indicators all students (100%) have a high motivation